Elevated Activity and Microglial Expression of Myeloperoxidase in Demyelinated Cerebral Cortex in Multiple Sclerosis - Gray, Elizabeth (Brain Pathol, 2007)
Recent studies have revealed extensive cortical demyelination in patients with progressive multiple sclerosis (MS). Demyelination in gray matter lesions is associated with activation of microglia. Macrophages and microglia are known to express myeloperoxidase (MPO) and generate reactive oxygen species during myelin phagocytosis in the white matter. In the present study we examined the extent of microglial activation in the cerebral cortex and the relationship of microglial activation and MPO activity to cortical demyelination. Twenty‐one cases of neuropathologically confirmed multiple sclerosis, with 34 cortical lesions, were used to assess microglial activation. HLA‐DR immunolabeling of activated microglia was significantly higher in demyelinated MS cortex than control cortex and, within the MS cohort, was significantly greater within cortical lesions than in matched non‐demyelinated areas of cortex. In homogenates of MS cortex, cortical demyelination was associated with significantly elevated MPO activity. Immunohistochemistry revealed MPO in CD68‐positive microglia within cortical plaques, particularly toward the edge of the plaques, but not in microglia in adjacent non‐demyelinated cortex. Cortical demyelination in MS is associated with increased activity of MPO, which is expressed by a CD68‐positive subset of activated microglia, suggesting that microglial production of reactive oxygen species is likely to be involved in cortical demyelination.